Persepsi Karyawan Tentang Etika Bisnis (Studi Pada PT Angkasa Pura I Bandar Udara Sam Ratulangi) - Riane Johnly Pio; Johny Revo Elia Tampi (Universitas 17 Agustus 1945 Jakarta, 2018)
The purpose of this study is to determine employee perceptions of business ethics, ethical implementation and local cultural values by employees. Data were obtained from 92 respondents by using questionnaires at nominal scale, which were analyzed using nonparametric statistics. The results showed that employee perception about business ethics is very good because the majority of respondents gave a positive answer on the indicators tested in the range of numbers 73% to 98%. The implementation of binsis ethics in air transport services company is quite good because of lack of complaints from customers. While the impact of local cultural values on ethical behavior is relatively less visible because the strategy and business policy set from the head office. Therefore, knowledge and understanding of employee business ethics need to be improved, as well as the availability of ethical guidebooks for the implementation of business ethics to be easily realized, and local cultural values need to be integrated with organizational business practices